Enhanced in vitro refolding of fibroblast growth factor 15 with the assistance of SUMO fusion partner. - Bo Kong; Grace L Guo (PLoS ONE, 2011)
Fibroblast growth factor 15 (Fgf15) is the mouse orthologue of human FGF19. Fgf15 is highly expressed in the ileum and functions as an endocrine signal to regulate liver function, including bile acid synthesis, hepatocyte proliferation and insulin sensitivity. In order to fully understand the function of Fgf15, methods are needed to produce pure Fgf15 protein in the prokaryotic system. However, when expressed in Escherichia coli (E. coli), the recombinant Fgf15 protein was insoluble and found only in inclusion bodies. In the current study, we report a method to produce recombinant Fgf15 protein in E. coli through the use of small ubiquitin-related modifier (SUMO) fusion tag. Even though the SUMO has been shown to strongly improve protein solubility and expression levels, our studies suggest that the SUMO does not improve Fgf15 protein solubility. Instead, proper refolding of Fgf15 protein was achieved when Fgf15 was expressed as a partner protein of the fusion tag SUMO, followed by in vitro dialysis refolding. After refolding, the N-terminal SUMO tag was cleaved from the recombinant Fgf15 fusion protein by ScUlp1 (Ubiquitin-Like Protein-Specific Protease 1 from S. cerevisiae). With or without the SUMO tag, the refolded Fgf15 protein was biologically active, as revealed by its ability to reduce hepatic Cyp7a1 mRNA levels in mice. In addition, recombinant Fgf15 protein suppressed Cyp7a1 mRNA levels in a dose-dependent manner. In summary, we have developed a successful method to express functional Fgf15 protein in prokaryotic cells.